2001
DOI: 10.1385/bter:83:3:231
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Serum Selenium in Pregnant Women with Gestational Diabetes Mellitus

Abstract: Gestational diabetes is one of the most common diseases in pregnancy. In the present work, the possible relationship between serum selenium concentration and gestational diabetes was investigated. Blood samples of 234 pregnant women were collected, including 98 subjects with impaired glucose tolerance (IGT), 46 subjects with gestational diabetes mellitus (GDM), and 90 normal pregnant women (NPW). An additional 17 samples of normal women of fertile age (NW) were collected for comparison. The hydride generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 7 publications
3
52
0
Order By: Relevance
“…Our study showed that the selenium level of gestational diabetes and intolerant pregnancies was lower than that of normal pregnant women. The results were similar to the reports of previous researches [5][6][7][8]. The results from both studies demonstrated that selenium is a very important element for glucose intolerants, and its deficiency could aggravate diabetes in the gestational period and increase diabetic complications.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study showed that the selenium level of gestational diabetes and intolerant pregnancies was lower than that of normal pregnant women. The results were similar to the reports of previous researches [5][6][7][8]. The results from both studies demonstrated that selenium is a very important element for glucose intolerants, and its deficiency could aggravate diabetes in the gestational period and increase diabetic complications.…”
Section: Discussionsupporting
confidence: 90%
“…These decreases are greater in pregnant women with gestational or pre-existing diabetes. A lower level of selenium has been described in GDM, and it has been shown that there was a inverse relationship with this trace element status and glucose tolerance [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Many epidemiological studies demonstrated that serum Se levels were lower in diabetic patients than in healthy individuals. [17][18][19] The atrophy and degeneration of pancreatic islets have also been reported in patients with the Se-deficiency syndrome, Keshan disease.…”
Section: )mentioning
confidence: 91%
“…Many epidemiological studies have proved that serum Se levels in diabetic patients are lower than the levels in healthy individuals. [14][15][16][17][18] The atrophy and degeneration of pancreatic islets are observed in patients with a Se deficiency syndrome, Keshan disease. 19) Se-insufficient rats have low serum insulin levels, which are normalized by Se-supplementation.…”
Section: Introductionmentioning
confidence: 99%